Animal remains from the Early Makurian cemetery in el-Zuma(season 2013) - Urszula Iwaszczuk (Polish Archaeology in the Mediterranean, 2016)
Excavation in 2013 of two tumuli, T.15 and T.21, making up part of the Early Makuriancemetery at El-Zuma, yielded numerous animal bones among other finds. The total from T.15 wasa set of 1404 fragmentary bones belonging (with the exception of 653 that could not be identifieddue to the poor state of preservation) to cattle and ovicaprids. The remains came from the shaft,the burial chamber and two lateral chambers. The number of bones from T.21 was much smaller,restricted to 78 fragments, coming mostly from the burial chamber. Except for one bird bone andseven unidentified fragments, the remains belonged to an ovicaprid. Marks visible on the bonesfrom both tumuli confirmed that the parts of cattle and ovicaprine carcasses served as food offeringsfor the dead.